Investigação dos mecanismos associados ao efeito cicatrizante e regenerativo do barbatimão (Stryphnodendron adstringens) em modelos celulares in vitro - Pellenz, Neida Luiza Kaspary (2019)
Introduction: The skin is the largest organ of the human body and has the functions of coat, delimitate, protec and interact with the external environment. Skin lesions affect the general population, regardless of gender, age or ethnicity, and because of the high rate of people with changes in skin integrity, it is a serious public health problem. The healing of lesions is considered a process of restoration of the homeostasis of the skin, dynamic and highly coordinated, and in recent years there has been a resumption to the valorization of therapeutic practices with the use of herbal medicines in the treatment of various morbidities, including cicatrization of cutaneous lesions. Many plants have already shown promise, especially barbatimão (Stryphnodendron adstringens), several in vitro and in vivo studies have already been performed demonstrating the healing and anti-inflammatory action, however the related mechanisms have not yet been clarified. Objective: To analyze in vitro the causal mechanisms associated with the healing effect of barbatimão (Stryphnodendron adstringens), as well as to carry out literature review and analyze a series of related cases. Methods: Initially, an integrated analysis of the literature related to the healing properties of barbatimão was performed, considering the data available in the main scientific platforms as well as the analysis of a series of cases. The barbatimão shells were obtained, and the hydroalcoholic extract was prepared and characterized chemically via High Performance Liquid Chromatography (HPLC). The extract was tested in vitro in two commercial keratinocyte (HaCaT) and fibroblast (HFF-1) cell lines, grown in an appropriate environment, the pharmacological curves were performed, and once the concentrations of use were determined, analyzes were performed related to cytotoxicity and genotoxicity. In a third phase, the HFF-1 cells, integrals and in vitro lesion model, treated with barbatimão at concentrations of 0.49mg / mL and 0.99mg / mL for 24 or 72 hours, were evaluated: (1) oxidative metabolism (oxidation of DNA, lipoperoxidation, carbonylation of proteins, levels of antioxidant enzymes); (2) proinflammatory cytokines (TNF-α, interleukin 6); (3) apoptotic markers = Caspases (CASPs) 3 and 8 and growth factors (KGF and FGF-1). Results: 42 publications on barbatimão were included in the review, most published in English. From these studies a description of several biological and clinical actions of barbatimão was identified, such as anti - inflammatory, anti - oxidant, antiulcerogenic and antimicrobial effects, antiparasitics, and its curative properties. We report a series of cases of patients submitted to barbatimão for healing of injuries caused by intense involuntary physical trauma (external accidents) or surgery. Considering all cases, the complete duration of healing occurred for 3.6 ± 0.8 months. In relation to study 2, the results demonstrate that the main bioactive molecules quantified by HPLC were gallic acid, caffeic acid, quercetin, catechin and epigallocatechin-3-gallate (EGCG). The barbatimão was able to decrease the cellular mortality in comparison with the control group, and still presented genoprotective effect to the DNA. In the third study, the treatment with 0.49 mg / mL and 0.99 mg / mL presented a reducing effect on the oxidative, inflammatory and apoptotic markers, concomitantly the barbatimão was able to raise the levels of antioxidants and growth factors. Conclusion: In view of the literature review, the case series, and our in vitro studies, our initial results, which need to be complemented by further studies, give strong indications of the antioxidant, genoprotective, anti-inflammatory, anti -apoptotic, and pro-growth factors of barbatimão, which could explain the efficacy of this herbal medicine in the healing of lesions.